Solution of dynamic power flow technique considering governor nonlinearity. (10th September 2019) - Fan, Chengwei; Chen, Zhen; Wang, Xiaoru; Teng, Yufei; Chen, Gang; Zhang, Hua
Summary: An improved dynamic power flow (DPF) model considering governor nonlinearity is presented. The proposed DPF model is intended for the analysis of post‐contingency power flow after primary frequency regulation. During the regulation process, the governors play an important role while it is difficult to involve the nonlinear segments in the static method. So in this paper, the governor model with amplitude‐limit and deadband is simplified and included in DPF model. Using the describing function method, the effect of deadband is equivalent to an increment of regulation coefficient. The amplitude‐limit is handled by iterative correction. Applying the algorithm to a three‐node system, a case study of load variation proves the effectiveness of the algorithm. Simulations on a practical grid in southern China further demonstrates the practicability and applicability. The algorithm enhances the accuracy of post‐contingency power flow analysis and provides effective analysis for the static security of power system.